Building a personal brand on social media - Curtis, Robin (2021)
This bachelor thesis analyses branding techniques for the creation of strong brand equity and a cohesive brand identity for individuals seeking to use social media in order to generate revenue through a personal brand. The purpose of this work is to create a personal brand on social media for myself with the use of theoretical knowledge gained throughout the thesis. The first part examines how leading branding experts create brand equity and a strong brand identity in order to create loyal customers. The second part takes a look at personal branding, contrasting it to that of corporate branding and analyses methods how individuals can differentiate themselves and use social media to create brand trust, brand visibility and revenue generating streams. The practical part of the thesis is dedicated to defining and creating a cohesive personal brand and the monetisation opportunities for myself.